Mass Mortality of Fish in Lampung Bay, Indonesia - Tumpak Sidabutar (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2016)
The surface waters in Lampung Bay appeared with dark reddish brown color from the beginning of October until November 2012 due to a bloom, an explosion in the phytoplankton population. This event resulted in the mass mortality of fishes that are cultured in floating nets there. Other smaller and less frequent blooms occurred in the bay the next year. This algal bloom was caused by the dinoflagellate species Cochlodinium polykrikoides. This was thought to be the first bloom of Coclodinium in these waters, or any in Indonesian waters. The highest abundance of Cochlodinium during the incident reached to 3.07 x 107 cells.l-1. Mass fish mortality in the floating nets was due to oxygen depletion, mainly during the night time. The clogging of their gills by dense phytoplankton cells was assumed to be the cause. The population explosion of Cochlodinium was triggered by a high ratio of nitrate and phosphate concentration in the waters. The nutrient ratios of N/P in the water were high, indicating nitrate as a triggering factor and phosphate as a limiting factor.Keywords: algal bloom, Cochlodinium, discoloration, fish mortalities, Lampung Bay